Athletic Identity and the Transition Out of Sport among Division I Football Players - Manswell, Mykal; Barnicle, Scott P (Journal of Sports Research, 2018)
Athletic identity is a key factor in multiple areas in a student-athlete’s career however, athletic identity is both fragile and critical simultaneously, effecting things such as self-confidence, self-identity, and reputation around campus. Through interviews with 10 football players at a Mid-Atlantic American Division 1 University, qualitative data was gathered examining interests outside of the sport, their process of becoming a Division 1 athlete, and preparation for life after football. Primary findings explored common trends among the participants such as shared long-term goals, sport attached identity, and the absences of post athletic-career skills, or even exposure to such skill training at their university. Additional results suggested participant student-athletes have a solid sense of who they are but do not have a stable outlet for who they want to become outside of sport. This study can inform universities that student athletes not only desire innovative methods for career development, but also possess diverse ideas for their future beyond the student-athlete experience.